An automated method of producing of a picturesque three-dimensional map image - German, Anna R.; Atayan, Larysa V. (Journal of the Belarusian State University. Geography and Geology, 2017)
The method of producing of a picturesque three-dimensional (3D) map image using programs for vector and raster graphics is considered. The subsequent construction of three-dimensional images consisting of several stages (preparatory, field, and laboratory phase) is shown. The creation of three-dimensional image begins with the study of the territory according to aero- and space images, freely available on the Internet. Their analysis and interpretation allow defining a point of view and coverage of the territory, which should be represented on the 3D map (the preparatory phase). A field survey of the area is performed if it is necessary (the field phase). Directly the construction of map image is performed in laboratory conditions (the laboratory phase) and it includes several types of work. First of all, the plan of the area is created. After-wards it is converted into a perspective image in the program Adobe Illustrator. The outline drawing (frame of buildings) is implemented on the basis of the Perspective grid tool and then is detailed. For these purposes, the pre-created library of graphic symbols of the first order and signs of higher order is used. The process of creating of 3D image is finished by his color design which can be performed both using only image editors (Adobe Illustrator, Adobe Photoshop), and the combined hand-automatic way. Previously the library of textures and color palettes, which also included light and shadow, is developed in digital form in program of raster graphics. Using the rules of constructing shadows and gradations of light, it is possible to achieve an expressive and volumetric image, depending on the surface texture of the object. The application of this methodology allows to create the complete view of the three-dimensional image and to give it picturesqueness and realism. The picturesque three-dimensional map image, having visual properties, can be widely used in the field of tourism both in the traditional paper editions and in electronic applications of various subjects.
Keywords: automation; three-dimensional map image; structural elements; perspective; the library of symbols, tex- tures, and palettes